Clinical Features of Headache in Patients With Diagnosis of Definite Vestibular Migraine: The VM-Phenotypes Projects - Teggi, Roberto; Colombo, Bruno; Albera, Roberto; Asprella Libonati, Giacinto; Balzanelli, Cristiano; Batuecas Caletrio, Angel; Casani, Augusto P.; Espinosa-Sanchez, Juan Manuel; Gamba, Paolo; Lopez-Escamez, Jose A.; Lucisano, Sergio; Mandalà, Marco; et al. (Frontiers in Neurology, 2018)
Migraine is a common neurological disorder characterized by episodic headaches with specific features, presenting familial aggregation. Migraine is associated with episodic vertigo, named Vestibular Migraine (VM) whose diagnosis mainly rely on clinical history showing a temporary association of symptoms. Some patient refers symptoms occurring in pediatric age, defined “episodic symptoms which may be associated with migraine”. The aim of this cross sectional observational study was to assess migraine-related clinical features in VM subjects. For the purpose, 279 patients were recruited in different centres in Europe; data were collected by a senior neurologist or ENT specialist through a structured questionnaire. The age of onset of migraine was 21.8±9. The duration of headaches was lower than 24 hours in 79.1% of cases. Symptoms accompanying migrainous headaches were, in order of frequency, nausea (79.9%), phonophobia (54.5%), photophobia (53.8%), vomiting (29%), lightheadedness (21.1%). Visual or other auras were reported by 25.4% of subjects. A familial aggregation was referred by 67.4%, while migraine precursors were reported by 52.3% of subjects. Patients reporting nausea and vomiting during headaches more frequently experienced the same symptoms during vertigo. Comparing our results in VM subjects with previously published papers in migraine sufferers, our patients presented a lower duration of headaches and a higher rate of familial aggregation; moreover some common characters were observed in headache and vertigo attacks for accompanying symptoms like nausea and vomiting and clustering of attacks.